2008
DOI: 10.1515/znc-2008-5-603
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Kaurane Diterpenes against Oral Pathogens

Abstract: Two kaurane diterpenes, ent-kaur-16(17)-en-19- , respectively. Our results show that KA has potential to be used as a prototype for the discovery of new effective anti-infection agents against microorganisms responsible for caries and periodontal diseases. Moreover, these results allow to conclude that minor structural differences among these diterpenes significantly influence their antimicrobial activity, bringing new perspectives to studies on the structure-activity relationship of this type of metabolites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 23 publications
4
56
0
Order By: Relevance
“…Members of this class of diterpenes have also been reported to have cytotoxic effects [6,7], antiproliferative action on tumour cell cultures [8], and significant antibacterial and antifungal activities, including effect against phytopathogenic fungi [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Members of this class of diterpenes have also been reported to have cytotoxic effects [6,7], antiproliferative action on tumour cell cultures [8], and significant antibacterial and antifungal activities, including effect against phytopathogenic fungi [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These agents are safer and are free from side effects which are observed in case of the antibiotics and mouth rinses. Researchers have revealed the potential of a number of plants against cariogenic bacteria [9][10][11][12][13][14][15][16][17][18][19][20] . In the present study, the leaf extract of Jasminum arborescens was shown to possess antibacterial activity against clinical isolates of S. mutans recovered from dental caries subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The time necessary for growth was 24 h for E. faecalis and A. actinomycetemcomitans, and 96 h for anaerobic bacteria, incubated at 37°C in appropriate gaseous conditions (facultative in aerobic condition; microaerophilic in an atmosphere of 10% CO 2 ; anaerobic bacteria in the anaerobic workstation Don Whitley ScientiWc, Bradford, UK, in an atmosphere of 5-10% H 2 , 10% CO 2 , 80-85% N 2 ). After that, resazurin (30 l) in aqueous solution (0.02%) was added to the microplates, to indicate microorganism viability [1]. Before addition of resazurin and to determine MBC, an aliquot of the inoculum was aseptically removed from each well showing no apparent growth, then plated onto Schadler agar (Difco, Kansas City, MO) supplemented with hemin (5 g/ml), vitamin K1 (10 g/ml), and sheep blood (5%) for anaerobic bacteria.…”
Section: Structure Determination Of Compoundsmentioning
confidence: 99%